2019
DOI: 10.1111/evj.13159
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shockwave therapy raises mechanical nociceptive threshold in horses with thoracolumbar pain

Abstract: Summary Background Although extracorporeal shockwave therapy (ESWT) is a common treatment for horses with back pain, effects on mechanical nociceptive threshold (MNT) and multifidus muscle cross sectional area (CSA) in the spine are unknown. Objectives To evaluate effects of ESWT on spinal MNT and multifidus muscle CSA in horses with thoracolumbar pain. Study design Non‐randomised trial. Methods Thoracolumbar spines of 12 horses with thoracolumbar pain were radiographed to document existing pathology. Each hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 36 publications
0
35
0
1
Order By: Relevance
“…However, this finding is in line with ours' as well as others' clinical impression that there is tremendous individual variability on palpation of the thoracolumbar region. Mechanical nociceptive threshold of the dorsum additionally has no relationship with radiographic evidence of either ORDSP or pathology of the thoracic articular facets, as previously discussed . Pain on palpation of the dorsum may therefore not be a sensitive diagnostic for identification of pain directly attributable to thoracolumbar pathology; this underscores the necessity of diagnostic analgesia in combination with other diagnostics for accurate diagnosis of clinically relevant ORDSP …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, this finding is in line with ours' as well as others' clinical impression that there is tremendous individual variability on palpation of the thoracolumbar region. Mechanical nociceptive threshold of the dorsum additionally has no relationship with radiographic evidence of either ORDSP or pathology of the thoracic articular facets, as previously discussed . Pain on palpation of the dorsum may therefore not be a sensitive diagnostic for identification of pain directly attributable to thoracolumbar pathology; this underscores the necessity of diagnostic analgesia in combination with other diagnostics for accurate diagnosis of clinically relevant ORDSP …”
Section: Discussionmentioning
confidence: 90%
“…Mechanical nociceptive threshold of the dorsum additionally has no relationship with radiographic evidence of either ORDSP or pathology of the thoracic articular facets, as previously discussed. 31 Pain on palpation of the dorsum may therefore not be a sensitive diagnostic for identification of pain directly attributable to thoracolumbar pathology; this underscores the necessity of diagnostic analgesia in combination with other diagnostics for accurate diagnosis of clinically relevant ORDSP. 8,19 For the purposes of the study reported here, successful long-term outcome was defined as improvement in clinical signs described prior to surgical intervention rather than return to work at a similar or higher level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracolumbar pain and associated neuromuscular dysfunction are common clinical entities in the athletic horse [1][2][3]. A great variety of specific disorders may cause thoracolumbar pain in horses, and affect several anatomical structures in the area, i.e., bones, muscles, joints and ligaments, although the most common disorders are the impingement of the dorsal spinous processes and osteoarthritis of the articular facets [4][5][6]. Regardless of the source/s of back pain, some authors have described the pathophysiological pattern of back pain in horses by extrapolating the knowledge and consequences of low back pain in human beings.…”
Section: Introductionmentioning
confidence: 99%
“…It was recommended that such neuromodulation ‘.... be considered for the management of trigeminal‐mediated headshaking in horses ......’. In the second example, back pain in 12 horses was treated with extracorporeal shockwave therapy; the effect on pain was evaluated using the change in mechanical nociceptive threshold. All horses were treated and there was no control group.…”
mentioning
confidence: 99%